Formulation and physicochemical and organoleptic analysis tofu as additional materials in making steamed brownies - Mohammad Thariq Santriadi; Anies Asmediana; Wendianing Putri Luketsi (Universitas Darussalam Gontor, 2020)
Tofu is asoft solidfoodmaterial madefrom soybeans and rich in protein. So tofu can be applied as an additional ingredient in making steamed brownies. The purpose of this study was to obtain a formulation of steamed brownies with the addition of tofu which was accepted by panelists. In addition, this study also aims to determine the effect of tofu on the chemical and physical properties of steamed brownies. This study uses preliminary research with an experimental method of making brownies with the addition of tofu which is divided into 3 different samples based on the number of tofu additions namely 37.5gr, 75gr and 112.5gr and further research is organoleptic, chemical and physical tests. The experimental design in this study was a completely randomized design (CRD) with 2 replications of samples and 2 replications of analysis. The results of the organoleptic test showed that steamed brownies with the addition of the most dominant tofu was F1 with the addition of tofu 37.5 gr byassessing the attributes of taste (6.3%), color (6.1%), texture (6.3%) and aroma (5, 5%). Physical tests show that more tofu additions can affect the development ratio and specific volume of the dough. F1 steamed brownies contain water (36.16%), total sugar (35.32%), protein (0.20%). Steamed Brownies F2 contain water (36.84%), total sugar (23.55%), protein (0.30%). While the F3 steamed brownies contain water (39.50%), total sugar (6.81%), protein (0.33%).The steamed brownies with the addition of tofu werethe most preferred by panelists through testing the attributes of aroma, color, texture and taste, namely F1 with the addition of tofu 10% or as much as 37.5 grams